Diversidade genética de quatro linhagens de Oreochromis niloticus utilizando o marcador RAPD - Massago, Haluko [UNESP]; Ribeiro, Ricardo Pereira; Lopera Barrero, Nelson Mauricio; Povh, Jayme Aparecido; Castagnolli, Newton; Gomes, Patricia Cristina (Universidade Federal de Uberlândia (UFU), 2009)
The aim of this study was to analyze the genetic diversity of four Nile Tilapia (Oreochromis niloticus) strains using the RAPD marker. Fin samples of GIFT (G), Chitralada (C), Supreme (S) and Bouake (B) juvenile stocks have been collected. The 11 primers used yielded 81 fragments of which 41.98% were polymorphic. The percentage of polymorphic loci (G: 18.52%; C: 19.75%; S: 20.99% and B: 24.79%) showed that there was a genetic differentiation among the strains, showing the G(st) values a high (BxG: 0.231; BxC: 0.224; GxC: 0.194 and SxC: 0.208) and elevated (BxS: 0.315 and GxS: 0.270) differentiation. The highest gene flow (N(m)) was among the GxC (2.082) strains. The distance and genetic identity values (0.044 and 0.957 respectively) and the dendrogram indicate that the GxC is the most genetically similar strains. The genetic similarity was high among of the strains (G: 0,932; C: 0,903; S: 0,891 and B: 0.900). These results will enable a correct reproductive and genetic strains management.

O objetivo do presente estudo foi analisar a diversidade genética de quatro linhagens de tilápia do Nilo (Oreochromis niloticus) utilizando o marcador RAPD. Foram coletadas amostras de nadadeira de estoques de juvenis das linhagens GIFT (G), Chitralada (C), Supreme (S) e Bouaké (B). Os 11 primers utilizados produziram 81 fragmentos dos quais 41,98% foram polimórficos. A porcentagem de fragmentos polimórficos (G: 18,52%; C: 19,75%; S: 20,99% e B: 24,79%) confirmaram que houve uma diferenciação genética entre as linhagens, mostrando os valores de Gst uma alta (BxG: 0,231; BxC: 0,224; GxC: 0,194 e SxC: 0,208) e elevada (BxS: 0,315 e GxS: 0,270) diferenciação. O fluxo gênico (Nm) foi maior entre as linhagens GxC (2,082). Os valores de distância e identidade genética (0,044 e 0,957 respectivamente) e o dendrograma indicam que as linhagens GxC são os mais semelhantes geneticamente. A similaridade genética foi alta dentro das linhagens (G: 0,932; C: 0,903; S: 0,891 e B: 0.900). Os resultados deste estudo possibilitarão o correto manejo reprodutivo e genético das linhagens.
Genetic diversity of four Oreochromis niloticus strains using the rapd marker
Keywords: Bouake; Chitralada; Genetic variability; GIFT; Supreme; Tilapia